كاريگه‌ريى ڕه‌گه‌زه‌ ئاووهه‌واييه‌كان له‌سه‌ر ڕاماڵين له‌ پارێزگاى سلێمانى - زه‌نگه‌ن, بشرى قادر كريم (Sulaimani Journal for Humanities, 2018)
In this study, we show the impact of weather elements on the rate of erosion in Sulaimaniah District. Various data ware obtained from multiple weather stations including (Dukan, Chwarta, Penjween, Bazian, Sulaimaniyah and Darbandikhan) from the year 2003until 2015. The mass of water erosion was estimated based on Douglas equation, the power of water erosion was found through Fournier equation and wind erosion was calculated using Chepil equation as well as the geographical distribution in the area of study. Statistical analysis was performed using SPSS-14 to evaluate the degree of effect of weather elements on erosion rate. We conclude that rain fall is a positive factor that comes first in terms of its effect on size and power of water erosion (87.5% and99.5%), respectively. Furthermore, wind speed was found to be a positive factor on air erosion as rated 33.8%.